An insight into local environment of lanthanide ions in Sr2SiO4:Ln (Ln = Sm, Eu and Dy)1. (27th August 2015) - Gupta, Santosh K.; Nigam, Sandeep; Yadav, Ashok K.; Mohapatra, Manoj; Jha, Shambhu N.; Majumder, Chiranjib; Bhattacharyya, Dibyendu
<x xml:space="preserve">Abstract</x> Site occupancy of Eu2+, Eu3+, Sm3+ and Dy3+ is investigated in Sr2SiO4 using TRFS and EXAFS and complemented by DFT calculations.